A Tribute to Margaret Conrad: Activist, Scholar, Feminist Pioneer - Huskins, Bonnie (Atlantis)

(untitled) (Mount Saint Vincent University, 2010)
One of several presentations on Margaret Conrad's work and career at the 2009 Atlantic Canada Studies Conference in Charlottetown, this paper describes how Conrad applied her feminism to the writing, teaching and dissemination of history, and in the process, transformed the ways in which historians approach their profession.